BMP7 Functions to Regulate Proliferation of Dermal Papilla Cells in Hu Sheep - Yue Li; Xiaoyang Lv; Shanhe Wang; Xiukai Cao; Zehu Yuan; Tesfaye Getachew; Joram M. Mwacharo; Aynalem Haile; Wei Sun (Genes, 2022)
Bone morphogenetic proteins (BMPs) are the structurally similar and highly conserved type of functional proteins that play an important role in hair follicle growth and development. BMP7 was a differentially expressed gene in different patterns of Hu sheep lambskin identified using Agilent microarray. Since hair follicle is the basis of pattern formation of lambskin, and its growth and development is governed by dermal papilla cells (DPCs), to clarify the role of BMP7 and hair follicle, our study was designed to investigate the regulation between BMP7 and DPCs. Firstly, the CDS region of BMP7 was cloned by 3’Race and PCR in Hu sheep and performed serious of bioinformatic analysis. Then, the effects of BMP7 on DPCs were analyzed after overexpression and interference of BMP7 in dermal papilla cells by CCK8, EdU, and PI assay. Additionally, qPCR was also conducted to clarify the relationship between BMP7 and the TGF-β/Smad signaling pathway. A total of 1296 bp of the BMP7 CDS region sequence was sucessfully cloned in Hu sheep, encoding a signal peptide of 431 amino acids, molecular weight was 49,316.9 Da and the isoelectric point (Pi) was 7.75. Nucleotide sequencing analysis of BMP7 revealed that Hu sheep had high homology with Bos taurus, Homo sapiens, and Canis lupus familiaris. Structure domain prediction showed that TGF-β superfamily domain exist between 330th–431th amino acid, BMP7 protein is a secreted protein. In BMP7 up-regulated DPCs, DPCs proliferation rate and cell cycle were significantly higher than that of NC group (p < 0.05). Meanwhile, the expression level of Smad3, Smad4, Samd6, and TGF-β1 in TGF-β/Smad signaling pathway were significantly lower than that in NC group (p < 0.05). In BMP7 down-regulated DPCs, it presented the opposite result. In conclusion, our study showed that BMP7 had a positive effect on DPCs by accelerating the proliferation and cell cycle of DPCs, and hypothesized that regulate hair follicles growth and development via TGF-β/Smad signaling pathway. These findings may ...